Sociologia e gestão ambiental: considerações a partir de uma Reserva Extrativista Marinha - Maria Cristina Alves Maneschy; Tânia Guimarães Ribeiro; Edma Silva Moreira; Fernanda Valli Nummer; Ida Lenir Maria Pena Gonçalves (Ciências Sociais Unisinos)
In Brazil, Extractive Reserve is an environmental conservation unit. It is subject to a comanagement regime by residents, resources users, representatives of public and private agencies and civil society. This paper aims to understand how these actors interact to build this institution in a participatory way. It applies the sociological concepts of social networks, social and cultural capital, habitus and field, common resources management and interactive governance to the experience of the Caeté-Taperaçu Extractive Marine Reserve, in Bragança municipality, Pará State. The research employed a qualitative methodology, including document analysis about fisheries in the Amazonian seashore, semi-directive interviews with local fishermen and observations in meetings at the Association of Residents and Users of the Reserve during the year 2012. The social networks among users, especially fishermen, were incomplete, denser at the local level and with few external links, hence the contradiction between inshore fishery management and distant fishery deregulation. Yet, the growth of awareness of caring for the environment in the new territory is evident. The local committees, assemblies and the joint designing of rules and plans foster the interactive learning, despite the capital inequalities of the involved actors.